Food Waste and Byproducts: An Opportunity to Minimize Malnutrition and Hunger in Developing Countries - Torres-León, Cristian; Ramírez-Guzman, Nathiely; Londoño-Hernandez, Liliana; Martinez-Medina, Gloria A.; Díaz-Herrera, Rene; Navarro-Macias, Víctor; Alvarez-Pérez, Olga B.; Picazo, Brian; Villarreal-Vázquez, Maria; Ascacio-Valdes, Juan; Aguilar, Cristóbal N. (Frontiers in Sustainable Food Systems, 2018)
Food production and processing in developing countries generate high levels of waste and byproducts, causing a negative environmental impact and significant expenses. However, these biomaterials have ample potential for generating food additives and helping to minimize malnutrition and hunger in the developing countries where they are produced. Many of these biomaterials are a source of valuable compounds such as proteins, lipids, starch, micronutrients, bioactive compounds and dietary fibers. Additionally, antinutritional factors present in some byproducts can be minimized with biotech alternatives for use as a food additive or in the formulation of balanced foods. In this context, the use of these biomaterials is a challenge and a great opportunity to improve food security. The purpose of this review is to present the potential of food waste and byproducts as a sustainable alternative to reduce malnutrition and hunger in developing countries; some examples and perspectives are mentioned.